MEMBANGUN FONDASI LITERASI KEUANGAN SEJAK DINI: PROGRAM EDUKASI UNTUK ANAK USIA DINI - Hudaya, Robith; Akram, Akram; Hastuti, Ely Windarti; Fadhilah, Faiz (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The community service program entitled “Building the Foundation of Financial Literacy from an Early Age: An Educational Program for Early Childhood” was implemented to provide children with a basic understanding of wise financial management from an early age. Financial literacy in children is a crucial aspect in shaping healthy financial behavior in the future, and therefore needs to be introduced through educational, interactive, and age-appropriate approaches. The program was carried out through several methods, including socialization, training, technology implementation, mentoring, and evaluation. The socialization stage successfully raised awareness among teachers, parents, and the community about the importance of financial literacy. Training sessions equipped teachers and parents with practical skills to teach basic financial concepts through daily activities, interactive media, and educational simulations. The use of technology, such as simple applications, animated videos, and digital games, proved effective in helping children understand the concepts of saving, distinguishing between needs and wants, and using money wisely. Evaluation results showed that more than 70% of teachers and parents observed positive behavioral changes in children, particularly in their saving habits. The program also produced learning modules and established support groups to ensure its sustainability. Thus, this program not only improved the knowledge and skills of teachers and parents but also contributed significantly to building a strong foundation of financial literacy among early childhood children in a sustainable manner.